ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI LADA DI KECAMATAN TANJUNG RAJA, KABUPATEN LAMPUNG UTARA - Pranata, Yudi; Widjaya, Sudarma; Silviyanti, Serly (Jurnal Ilmu-Ilmu Agribisnis, 2019)
This research aims to analyze the household income and the prosperity grade of pepper farmers’ household in Tanjung Raja District of North Lampung Regency. This research was conducted in Tanjung Raja Village and Sinar Jaya Village of Tanjung Raja District, North Lampung Regency in January - February 2018 using a survey method. The samples were 62 pepper farmers taken by using simple random sampling. This research uses descriptive quantitative method to determine the income and the expenditure. Factors influencing the prosperity were analyzed by using binary logit in which the influential factors were found by looking at the significant values in Z-Statistics. The results showed that the household income of pepper farmers in the research area was categorized as high because the household income has reached for about two million five hundred thousand until three million five hundred thousand rupiah per month. The most contributed income was derived from pepper farming activities and the rest was contributed from non-pepper farming, off-farming, and non-farming activities. Based on BPS criteria, pepper farmer households at Tanjung Raja District were categorized as prosperous as many as 85.48 percent and were not prosperous as many as 14.52 percent. Based on the regression analysis using binary logit, there were two factors influencing the prosperity grade of pepper farmers, i.e household income and the number of jobs.Key words: household income, pepper farming, prosperity grade.